Government Strategy for Overcoming Poverty in Cilegon City, Indonesia - Leni Cahyani; Nia Karniawati (Universitas Muhammadiyah Yogyakarta, 2024)
Poverty is a complex and multidimensional social problem that affects the lives of millions of people throughout the world, including in the city of Cilegon. This research aims to explore the strategies used by the government to overcome poverty in the city. The research method used was qualitative analysis based on secondary data from government reports, literature studies, and interviews with relevant government officials. The research results showed that the Cilegon City government has implemented various strategies to reduce poverty levels, including social assistance programs, infrastructure development, education, skills training, and economic empowerment of local communities. However, there are still challenges in the implementation and effectiveness of these programs, including limited resources, inter-agency coordination, and community participation. Therefore, more coordinated and sustainable efforts are needed from the government and all stakeholders to increase the effectiveness and impact of poverty reduction strategies in Cilegon City.